Virtual health care center in Georgia - Kldiashvili Ekaterina; Schrader Thomas (BMC, 2008)
Abstract Application of telemedicine systems to cover distant geographical areas has increased recently. However, the potential usefulness of similar systems for creation of national networks does not seem to be widely appreciated. The article describes the "Virtual Health Care Knowledge Center in Georgia" project. Its aim was the set up of an online integrated web-based platform to provide remote medical consultations and eLearning cycles. The project "Virtual Health Care Knowledge Center in Georgia" was the NATO Networking Infrastructure Grant dedicated for development of telemedicine in non-NATO countries. The project implemented a pilot to organize the creation of national eHealth network in Georgia and to promote the use of innovative telemedicine and eLearning services in the Georgian healthcare system. In June 2007 it was continued under the NATO Networking Infrastructure Grant "ePathology - Virtual Pathology Center in Georgia as the Continuation of Virtual Health Care Center".